Study of Feed and habitat on Tarsius spectrum (Tarsier) in the Nature Reserve of Tangkoko â€“Batu Angus, North Sulawesi - WIRDATETI WIRDATETI; HADI DAHRUDIN (Society for Indonesian Biodiversity, 2006)
This research was conducted in the nature reserve on beach forest of Tangkoko Batu Angus. Study sites were located at 0 until 150 m above sea level. Data being collected were the type of feed, nest sites and habitat utilization. During the observation, 18 animals species were identified being consumed and consist of 77.7% insects, 16. 6% reptil and 5.5% bird. Fifty four species from 30 families were identified being habitat and eight species from four families were the nest of TarsierÂ© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: Tarsius spectrum, Feed, Habitat, Nature reserve, Tangkoko- Batu Angus